Explorative Study of Female Leadership Deficit in Indonesia - Dian Rezky Catur PITALOKA; Muhammad Irfan SYAEBANI; Maria ULPAH; Harryanto SUHARDJO (Communications of International Proceedings, 2020)
The lack of women's participation in top management positions is illustrated by the level of involvement that has eroded and the increase in jobs (Huang, Krivkovich, Starikova, Yee, and Zanoschi, 2019). The participation of women at higher levels or strategic positions in the company becomes essential because of the benefits it brings; in terms of social, political, and economics. Researchers want to explore how the Broken Rung phenomenon participates as a cause of Female Leadership Deficit in Indonesia. This study used a qualitative method with the Phenomenology approach. Retrieval of research data by conducting semi-structured in-depth interviews. Research analysis consists of four stages of coding, including open coding, axial coding, selective coding, and process coding. This research concludes that the Broken Rung is not found in Indonesia because before its system was unfair to females, there were already a few females in specific industries. The findings show that it happens due to job/industry stereotyping and self-discrimination by female itself.
Keywords: Broken Rung; Female Leader; Leadership; Gender Equality.